Estrategia psicopedagógica para abordar los comportamientos disruptivos en el contexto escolar. - Zambrano Zamora, Liyen Marina (2025)
The research focuses on the design and implementation of a psychopedagogical strategy to address disruptive behaviors in fourth and fifth grade students of General Basic Education at the Dr. Humberto Alvarado Prado School during the period 2024-2025, with the aim of improving school coexistence and optimizing the teaching-learning process. Starting from a psychopedagogical approach based on theories of development, learning and behavior, the main causes of disruptive behaviors were analyzed, such as the lack of socio-emotional skills, low tolerance to frustration and the absence of clear rules in the classroom. Through a qualitative and applied methodology, observations, interviews and questionnaires were carried out with teachers and students to identify behavioral patterns and design appropriate intervention strategies. The proposal includes emotional regulation techniques, strengthening of social skills, establishment of rules and positive reinforcement to improve classroom dynamics. It is expected that the application of this psychopedagogical strategy will contribute to the reduction of episodes of indiscipline, encourage student participation and strengthen the role of the teacher in classroom management. In conclusion, it is evident that a well-structured psychopedagogical intervention adapted to the needs of the group can generate a more harmonious, inclusive and conducive learning environment for the comprehensive development of students.